Penerapan Model Pembelajaran Make A Match Untuk Meningkatkan Hasil Belajar Ips Siswa Kelas V SD Negeri Saronsong - Kolopita, Riksan; Rorimpandey, Widdy H; Lompoliuw, Bobby A. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to improve student learning outcomes in social studies subjects through a Make A Match based learning model. This research uses the Classroom Action Research Method (PTK) which consists of planning, implementation, observation, reflection. The subjects of this research were class V students at Saronsong State Elementary School with a total of 13 students, consisting of 9 boys and 4 girls. Data collection techniques are written tests and observations. This research was carried out in 2 cycles. The research results showed that the first cycle achieved 64.23% learning completeness, and the second cycle reached 85.38%. Thus, it can be concluded that the application of the Make A Match model can improve student learning outcomes in social studies subjects on types of economic activities.